Effect of an anode modified with nitrogenous compounds on the performance of a microbial fuel cell. Issue 4 (16th February 2016) - Du, Haoyue; Bu, Yunfei; Shi, Yehui; Zhong, Qin; Wang, Juan
ABSTRACT: Three kinds of nitrogenous compounds (ammonium peroxydisulfate, ethylenediamine, methylene blue) were applied to modify graphite felt anodes in microbial fuel cells. All of the performances were greatly improved by modifying the anode surface. The maximum power density of the microbial fuel cell with modified anode was 355, 545, and 510 mW/m 2, respectively, which was larger than the ungroomed control (283 mW/m 2 ). The power density of microbial fuel cell with ethylenediamine-treated electrode was highest among the four microbial fuel cells. The increase of power density was correlated with the changes of N/C and O/C ratios on the anode according to the X-ray photoelectron spectrometry analysis.